Increased cardiac myocyte PDE5 levels in human and murine pressure overload hypertrophy contribute to adverse LV remodeling. - Sara Vandenwijngaert (Public Library of Science (PLoS), 2013)
Background The intracellular second messenger cGMP protects the heart under pathological conditions. We examined expression of phosphodiesterase 5 (PDE5), an enzyme that hydrolyzes cGMP, in human and mouse hearts subjected to sustained left ventricular (LV) pressure overload. We also determined the role of cardiac myocyte-specific PDE5 expression in adverse LV remodeling in mice after transverse aortic constriction (TAC). Methodology/principal findings In patients with severe aortic stenosis (AS) undergoing valve replacement, we detected greater myocardial PDE5 expression than in control hearts. We observed robust expression in scattered cardiac myocytes of those AS patients with higher LV filling pressures and BNP serum levels. Following TAC, we detected similar, focal PDE5 expression in cardiac myocytes of C57BL/6NTac mice exhibiting the most pronounced LV remodeling. To examine the effect of cell-specific PDE5 expression, we subjected transgenic mice with cardiac myocyte-specific PDE5 overexpression (PDE5-TG) to TAC. LV hypertrophy and fibrosis were similar as in WT, but PDE5-TG had increased cardiac dimensions, and decreased dP/dtmax and dP/dtmin with prolonged tau (P<0.05 for all). Greater cardiac dysfunction in PDE5-TG was associated with reduced myocardial cGMP and SERCA2 levels, and higher passive force in cardiac myocytes in vitro. Conclusions/significance Myocardial PDE5 expression is increased in the hearts of humans and mice with chronic pressure overload. Increased cardiac myocyte-specific PDE5 expression is a molecular hallmark in hypertrophic hearts with contractile failure, and represents an important therapeutic target.